Dangerous Games The Bolshoi and Yuri Grigorovitch - Jennings, Luke (Dance Books Ltd., Alton,Hampshire (UK), 2004)
Yuri Grigorovitch for the Bolshoi. The next played to the company's strengths with huge ensemble passages and the lavish deployment of swans in the lakeside acts. PALABRAS CLAVE: The Bolshoi, Yuri Grigorovitch, Swan Lake.
Dentro del apartado "It's Always Swan Lake".